2021
DOI: 10.3390/s21072338
|View full text |Cite
|
Sign up to set email alerts
|

Can EEG Be Adopted as a Neuroscience Reference for Assessing Software Programmers’ Cognitive Load?

Abstract: An emergent research area in software engineering and software reliability is the use of wearable biosensors to monitor the cognitive state of software developers during software development tasks. The goal is to gather physiologic manifestations that can be linked to error-prone scenarios related to programmers’ cognitive states. In this paper we investigate whether electroencephalography (EEG) can be applied to accurately identify programmers’ cognitive load associated with the comprehension of code with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 75 publications
4
26
0
1
Order By: Relevance
“…In other words, the ANS biomarkers could capture the cognitive load induced by the code comprehension and review as well as the EEG biomarkers could do. This result aligns with what Medeiros et al [82] have achieved, showing that EEG can assess programmers' cognitive load accurately. Still, its intrusiveness compared to ANS signals is less prevalent in practice and natural software development environments.…”
Section: Results Validation Using Eegsupporting
confidence: 90%
See 2 more Smart Citations
“…In other words, the ANS biomarkers could capture the cognitive load induced by the code comprehension and review as well as the EEG biomarkers could do. This result aligns with what Medeiros et al [82] have achieved, showing that EEG can assess programmers' cognitive load accurately. Still, its intrusiveness compared to ANS signals is less prevalent in practice and natural software development environments.…”
Section: Results Validation Using Eegsupporting
confidence: 90%
“…Although plenty of papers show that HRV and Pupillography can be used to measure cognitive load (e.g., [18][19] [20]) we want to ensure further that they can be applied to intellectually complex and abstract tasks such as code reviews. Medeiros et al [82] showed that EEG biomarkers could be used to finetune or validate the results obtained with ANS signals, which can be acquired using non-intrusive wearable devices.…”
Section: Results Validation Using Eegmentioning
confidence: 99%
See 1 more Smart Citation
“…2) BASE Dataset: BASE dataset is composed by 2,340 ICs obtained from EEG signals recorded during code comprehension in a cognitive load assessment study from BASE project [53], [54]. This dataset contains short-term EEG signals, acquired from 30 subjects (24 males and 6 females, with ages ranging from 19 to 42 years), with an average duration of 9.45±3.92 minutes.…”
Section: A Datasetsmentioning
confidence: 99%
“…This region is an important part of the salience network, which not only drives attention toward target stimuli but also relates to decision-making and error-monitoring ( Droutman et al, 2015 ; Lamichhane et al, 2016 ; Bastin et al, 2017 ; Billeke et al, 2020 ). Our previous study suggests that the insula is activated for challenging deep-level analysis of code inspection and demanding error-monitoring ( Castelhano et al, 2019 ; Medeiros et al, 2021 ). Moreover, the use of mathematical- or reading-related skills to source-code understanding has been a matter of recent studies ( Prat et al, 2020 ; Castelhano et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%